Live Attenuated Vaccine Based on Duck Enteritis Virus against Duck Hepatitis A Virus Types 1 and 3 - Zou, Zhong; Ma, Ji; Huang, Kun; Chen, Huanchun; Liu, Ziduo; Jin, Meilin (Frontiers in Microbiology, 2016)
As causative agents of duck viral hepatitis, duck hepatitis A virus type 1 (DHAV-1) and type 3 (DHAV-3) causes significant economic losses in the duck industry. However, a licensed commercial vaccine that simultaneously controls both pathogens is currently unavailable. Here, we generated DEV recombinants (rC-KCE-2VP1) containing both VP1 from DHAV-1 (VP1/DHAV-1) and VP1 from DHAV-3 (VP1/DHAV-3) between UL27 and UL26. A self-cleaving 2A-element of FMDV was inserted between the two different types of VP1, allowing production of both proteins from a single open reading frame. Immunofluorescence and Western blot analysis results demonstrated that both VP1 proteins were robustly expressed in rC-KCE-2VP1-infected chicken embryo fibroblasts. Ducks that received a single dose of rC-KCE-2VP1 showed potent humoral and cellular immune responses and were completely protected against challenges of both pathogenic DHAV-1 and DHAV-3 strains. The protection was rapid, achieved as early as three days after vaccination. Moreover, viral replication was fully blocked in vaccinated ducks as early as one week post-vaccination. These results demonstrated, for the first time, that recombinant rC-KCE-2VP1 is potential fast-acting vaccine against DHAV-1 and DHAV-3.